ACCOUNTING AND RISING PRICES IN A STUDENT CO–OPERATIVE. - Corbin, Donald A. (The Accounting Review, 1951)
All business firms have felt the impact of rising prices in one way or another. In many cases their financial statements have yielded peculiar results. On the balance sheet, the historical cost basis of valuation of plant and equipment, and the "lower of cost or market" method for the valuation of inventories have tended to undervalue assets grossly. Credit ratings, current ratios, and insurance coverage often cannot be determined adequately from these figures. On the income statement, reported earnings have often soared to unprecedented heights, due mainly to the matching of out of date inventory and depredation figures against current, higher selling prices. Accompanying this exaggeration of profits are the problems of higher replacement costs of inventories and plant, of sharing these illusory profits among the government taxing agencies, laborers, and stockholders, of the determination of future selling prices, etc. The accounting records become much less useful as aids in solving these perplexing problems, in as much as they have not been adapted to the changing price level.